Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 12 - Review - Page 908: 109



Work Step by Step

Step 1: $\ln 3x-\ln (x-3)=2$ Step 2: $\ln \frac{3x}{x-3}=2$ Step 3: $\frac{3x}{x-3}=e^{2}$ Step 4: $3x=e^{2}(x-3)$ Step 5: $3x-e^{2}x=-3e^{2}$ Step 6: $x(3-e^{2})=-3e^{2}$ Step 7: $x=\frac{-3e^{2}}{(3-e^{2})}$ Step 8: $x=\frac{3e^{2}}{e^{2}-3}$ Therefore, the solution set is {$\frac{3e^{2}}{e^{2}-3}$}.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.